1993
DOI: 10.3171/jns.1993.78.3.0470
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of angiogenesis and growth of human nerve-sheath tumors by AGM-1470

Abstract: The effectiveness of AGM-1470, a potent, fungal-derived inhibitor of angiogenesis, in suppressing the neovascularization and growth of human Schwann cell tumors was tested in six schwannomas, seven neurofibromas, and one neurofibrosarcoma. Tumor fragments from surgical specimens were implanted into the subrenal capsule of 348 nude mice (nu/nu). Seven days after implantation, the tumors were measured and vascularity was graded. The animals were then randomly assigned to one of two groups, to receive either sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Although inhibition of angiogenesis by TNP-470 has been demonstrated by a vascular grading system in human nerve sheath tumours (Takamiya et al, 1993), this study first showed that TNP-470 inhibited tumour angiogenesis in vivo quantitatively. This analysis system of tumour angiogenesis after hyperthermia seems a good model to study angiogenesis of murine tumour vasculature in vivo because hyperthermia at a high heat dose inevitably destroys murine tumour vasculature followed by angiogenesis.…”
Section: Tg Time Assaymentioning
confidence: 77%
“…Although inhibition of angiogenesis by TNP-470 has been demonstrated by a vascular grading system in human nerve sheath tumours (Takamiya et al, 1993), this study first showed that TNP-470 inhibited tumour angiogenesis in vivo quantitatively. This analysis system of tumour angiogenesis after hyperthermia seems a good model to study angiogenesis of murine tumour vasculature in vivo because hyperthermia at a high heat dose inevitably destroys murine tumour vasculature followed by angiogenesis.…”
Section: Tg Time Assaymentioning
confidence: 77%
“…TNP-470, a synthetic derivative of fumagillin, was shown to posses potent antiangiogenic activity and low toxicity in animal studies (5,6). Based on promising preclinical studies showing that TNP-470 inhibits the growth of solid tumors and prevents their metastasis (7)(8)(9)(10)(11)(12), this antiangiogenic compound was one of the earliest to enter antitumor clinical trials (13).…”
mentioning
confidence: 99%
“…Thus a bFGF-induced increase in tumour vascularity may stimulate tumour growth (30,31) or metastasis (32,33), particularly in the 38% of human colorectal carcinomas reported to have bFGF receptors (34). The possible bene ts of angiogenesis-enhanced chemotherapy delivery need to be balanced against the risks of accelerated tumour growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%